THE LYMPHOID TISSUES AND IMMUNE RESPONSES OF NEONATALLY THYMECTOMIZED MICE BEARING THYMUS TISSUE IN MILLIPORE DIFFUSION CHAMBERS - Osoba, David (The Rockefeller University Press, 1964)
Neonatally thymectomized mice were implanted intraperitoneally at 7 days of age with Millipore diffusion chambers containing either embryonic or neonatal thymus tissue. Mice which received either empty diffusion chambers or no further treatment following neonatal thymectomy served as controls. In contrast to these controls, most of the mice implanted with thymus-filled chambers gained weight satisfactorily, did not develop a wasting syndrome, and had the capacity to produce serum antibodies in response to sheep erythrocytes and to reject allogeneic skin grafts. Lymphoid follicles were present in the lymph nodes, spleen, and intestinal tract of the implanted mice but most still showed some diminution in the population of lymphocytes in both blood and tissues. Control thymectomized mice had markedly depleted lymphoid tissues and low peripheral blood lymphocyte levels. The tissue recovered after 1 to 2 months from the diffusion chambers showed only epithelial-reticular cells but no lymphoid cells. It is suggested that a humoral factor produced by the thymus epithelial-reticular complex may be responsible for endowing lymphoid cells with immunological competence.